“If English Was Good Enough for Jesus, It’s Good Enough for Me” - Kovacs, Peter (Paideusis, 2008)
Since the end of World War II, English has become the virtual lingua franca of the planet. However, this development carries significant ethical and educational questions: What are the consequences of the worldwide dominance of the English language? How has it affected and how will it affect the fortunes of other languages? What can and should we as educators to do to minimize or eliminate the harmful effects on some of the endangered languages of the world? This paper will invite educators into a philosophical discussion of the ethical complexities of teaching English as a Second or Foreign Language.